Backed Pieces and Their Variability in the Later Stone Age of the Horn of Africa - (:unkn) unknown (My University, 2020)
Backed pieces became widespread in the Upper Pleistocene and Holocene and are part of the classic definitions for the Later Stone Age in many parts of Africa. However, the association of backed pieces with Later Stone Age is not clear in the Horn of Africa. These pieces are present in both Middle Stone Age (MSA) and Later Stone Age (LSA) contexts. To what extent was the “backing phenomenon” homogeneous or diverse between and within the two periods? Here, we start with a review of the literature on backed pieces in the Horn of Africa, noting the lack of terminological consensus and the absence of a shared typology in the region. We then describe the variability of backed pieces using two complementary approaches: (1) multivariate statistical analysis on a set of 28 attributes of 188 artifacts from eight securely dated contexts and (2) 2D geometric morphometric analyses on the same dataset. The two approaches provide complementary results, which allow us to identify and discuss the chronological trends in backing technology and morphology, without introducing a new terminology or proposing a new formal “descriptive” typology.
Keywords: African Research